ANALYSIS OF POTENTIAL BANKRUPTCY USING THE ZMIJEWSKI METHOD IN TELECOMMUNICATION COMPANIES LISTED ON THE IDX FOR THE PERIOD OF 2018 – 2022 - Zehroh, Halimatus; Musa, Muh. Ichwan; Nurman; Ramli, Anwar; Budiyanti, Hety (Journal Management & Economics Review (JUMPER), 2023)
This study aims to analyze the potential for bankruptcy in telecommunications companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. The method used in this analysis is the Zmijewski method, which has been proven effective in identifying bankruptcy risks in companies. Financial data from telecommunication companies listed on the IDX during the study period were taken and analyzed. The results of the analysis show that there are several telecommunication companies that show bankruptcy potential. during the 2018-2022 period. Factors such as decreased profitability, increased debt, and low liquidity are the main causes of this potential bankruptcy. This research provides important information for telecommunications company stakeholders to better understand bankruptcy risk and take appropriate steps to deal with it. In addition, this research can also be a basis for developing more effective and sustainable bankruptcy prevention strategies.